GAMBARAN TINGKAT DEPRESI DAN OBESITAS PADA MAHASISWA FAKULTAS KEDOKTERAN ANGKATAN 2013 UNIVERSITAS WARMADEWA DENPASAR BALI - Putra, I Putu Eka Pramana (E-Jurnal Medika Udayana; Vol 5 No 5 (2016): E-jurnal medika udayana, 2016)
Depression is a psychiatric disorder that is influenced by psychosocial stress. Depression can include signs and symptoms, and diagnosis; it influenced how severe psychosocial stressors earned by individuals and the influence of the individual self. Levels of depression in adolescents has increased compared to the age of children and adults. In the depression has two eating disorders include anorexia and increased eating. This study aims to determine the relationship between depression and nutritional status in adolescents in the city of Denpasar. This research is a cross sectional design to the students of Warmadewa University students in 2013 who met the inclusion criteria. Total sample is 41 people. Measurement of depression through a questionnaire Beck Depression Index (BDI) and anthropometric nutritional status was measured using body mass index (BMI). The number of research subjects are female and male alike. On the nutritional status obtained 31 adolescents (64.6%) adolescents with mild obesity, 14 adolescents (29.2%) were obese and 3 adolescents (6.2%) with severe obesity. Interpretation of depression using the BDI, obtained 34 adolescents (70.8%) without interruption, 10 adolescents (20.8%) and mood disorders, and 4 teenagers (8.3%) with mild depression.
Keywords: Depression, obesity, college student.